Os desafios e as possibilidades de uma (re)leitura da responsabilidade civil a partir da emergência dos riscos produzidos pelas nanotecnologias - Gomes, Taís Ferraz (Universidade do Vale do Rio dos Sinos, 2011)
Civil liability and its assumptions as well has evolved to fit the social technological development, and the concomitant emergence of new damage to be protected from, especially the nanotechnologies both in the world and in Brazil. The movement to adjust this institute is marked by a joint responsible character consistent with the principle of the individuals? dignity, established in the First Article, subsection III, of the Brazilian Federal Constitution, by bringing together public right and private right. Nanotechnological potential damage is still unknown; what is already known is that nanotechnological responsibility can trigger potential harm. Despite not implemented by the Brazilian legal order yet, it has to be protected by the law. Alternatives encompass the usage of the general risk clause, the Consumer?s Rights Defense law abuse and provisions, some hypotheses of objective incidence liability always in consonance with the human person?s guardianship and by acknowledging the flexibility of civil liability assumptions: causal damage and nexus. Instances exist when precautionary measures will be advocated to prevent damage from occurring; in other instances the effective investigation of harm will be the departure point. For both hypotheses, to make the framing of nanotechnologies into the Brazilian Law viable open concepts have to be used, and hermeneutically developed criteria have to become the foundation. Society can not be left unprotected due to a lack of rules of law specific to nanotechnological liability. New liability has to be, first of all, judicious and, second of all, its outcomes must be protected, and the oddities of the actual case must always be abided by, a situation where previous understanding will be advocated.

La responsabilité civile et leurs bases ont évolué afin de s’adapter au développement technologique de la société contemporaine et à l’émergence des nouveaux dommages qui doivent être protegés, en particulier, des nanotechnologies aux niveaux mondial et brésilien. Le mouvement d’adéquation de cette conception de responsabilité est doté d’un caractère solidaire, en harmonie avec le principe de la dignité de la personne humaine, établi dans le premier article, III, de la Constitution Fédérale Brésilienne, en démontrant l’approche des droits public et privé. Le potentiel des dommages technologiques est aussi inconnu; cependant, on voit que la responsabilité technologique pourra entraîner des dommages potentiels et qu’elle, malgré la non positivation dans l’ordre juridique brésilien, devra être protégée par le Droit. Les alternatives seront l’usage de la clause générale du risque, de l’abus de droit et des dispositifs du Code de Défense du Consommateur, des hypothèses de l’incidence de responsabilité objective tujours en harmonie avec la tutelle de la personne humaine. On admet aussi la flexibilisation des présupposés de la responsabilité civile: le dommage et le lien de causalité. Il y a de cas où l’on demandera des mesures de précaution afin d’éviter l’occurrence de dommages, et d’autres où l’on partira d’une vérification effective d’un préjudice. Dans les deux hypothèses, la viabilité d’adaptation des nanotechnologies au Droit brésilien est seulement possible à travers de l’usage de concepts ouverts et à travers de critères herméneutiquement constitués. La société ne peut rester sans protection faute d’une règle juridique spécifique à la responsabilité nanotechnologique. Une nouvelle responsabilité “précaution” doit être, premièrement, prise et, après, leurs conséquences doivent être protégées, toujours observées les péculiarités du cas concret dont on demandera une précompréhension.
Keywords: Responsabilidade civil; Dignidade da pessoa humana; Nanotecnologias; Civil liability; Dignity of the human being; Nanotechnologies; Responsabilité Civile; Dignité de la personne humaine; Nanotechnologie; ACCNPQ::Ciências Sociais Aplicadas::Direito